THE ASSOCIATION BETWEEN BODY MASS INDEX AND DENTAL CARIES AMONG JUNIOR HIGH SCHOOOL STUDENTS IN BALIKPAPAN - Wulandari, Dian; Wirapuspita Wisnuwardani, Ratih (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Nutritional status and oral health are crucial aspects that influence the quality of life in adolescents. Body Mass Index (BMI) is often used as an indicator of nutritional status, while oral health status can be measured by the DMF index (Decayed, Missing, Filled). Objective : This study aimed to analyze the association between BMI and oral health among Balikpapan junior high school students. Research Methods/ Implementation Methods : This study used a cross-sectional design with a sample of 183 students from 7th and 9th grades in a junior high school. Statistical analysis utilized the Pearson correlation test to assess the association between BMI and DMF-T. Results : The results showed a statistically significant correlation between BMI and DMF scores (p = 0.039), indicating that variations in nutritional status might be associated with oral health conditions. Conclusion/Lesson Learned : Although there is a significant difference in BMI across certain nutritional categories, BMI is not directly associated with students' oral health. This study highlights the importance of school-based nutritional monitoring programs and oral health education to enhance the overall health of adolescents.